The Effectiveness of Using Chemistry Literacy-Based Learning Videos on the Problem-Solving Ability of Grade X Students at SMA Negeri 16 Batam - Nani Sudianti; Fetri Yeni J; Zulhendri Zen; Darmansyah; Emilham Mirshad; Abdul Habib Arrasyidi Desky (Jurnal Penelitian Pendidikan IPA, 2025)
Low understanding of subject matter, particularly in chemistry—especially in aspects of chemical literacy such as conceptual knowledge, contextual understanding, and higher-order thinking skills (HOTS)—combined with students’ limited problem-solving skills, has resulted in poor learning outcomes at SMA Negeri 16 Batam. Another contributing factor is the limited use of instructional media that supports real-life skill development. This study aimed to determine the effectiveness of chemistry literacy-based learning videos in improving the problem-solving abilities of Grade X students. The research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of two purposively selected classes: an experimental group taught using chemistry literacy-based videos and a control group using PowerPoint media. Research instruments included a chemical literacy test and a problem-solving skills test. Data were analyzed using an independent t-test to compare group results and an N-Gain test to evaluate treatment effectiveness. Findings revealed that the use of chemistry literacy-based videos significantly enhanced students’ chemical literacy, problem-solving skills, and overall learning outcomes compared to the control group. The N-Gain value of 73% categorized the intervention as moderately effective. Thus, chemistry literacy-based videos are effective instructional media for improving the quality of chemistry learning at the senior high school level.